Peran Guru dalam Menghadapi Kesulitan Belajar Anak Autisme di SLB Negeri Keleyan Bangkalan (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
teacher plays an important role in providing education, facilities, and learning conditions that are as optimal as possible. A good teacher is one who gives students enthusiasm for learning without any pressure. All humans have the right to get a decent education, including children with autism. Children with autism also have the right to receive educational services so that they gain knowledge and skills and can develop their potential. The aim of this research is to find out the role of teachers in overcoming the difficulties of children with autism at the SLB Keleyan Bangkalan. This is qualitative research with a descriptive method that uses data collection techniques through interviews and documentation. The subject of the research involves a teacher who teaches children with autism. The problems of autistic children that occur at SLB Keleyan cover three aspects, namely communication, behavior, and social interaction. So, that problems cause children with autism to become less focused on learning. However, at the SLB Keleyan Bangkalan, apart from focusing on learning, it also emphasizes that children are able to play and interact socially with the environment around them. Therefore, there are several treatments that teachers provide to overcome these learning difficulties without any reference or formula.